Linking Infectious and Narcology Care (LINC) in Russia: design, intervention and implementation protocol. Issue 1 (December 2016) - Gnatienko, Natalia; Han, Steve; Krupitsky, Evgeny; Blokhina, Elena; Bridden, Carly; Chaisson, Christine; Cheng, Debbie; Walley, Alexander; Raj, Anita; Samet, Jeffrey
Abstract Background Russia and Eastern Europe have one of the fastest growing HIV epidemics in the world. While countries in this region have implemented HIV testing within addiction treatment systems, linkage to HIV care from these settings is not yet standard practice. The Linking Infectious and Narcology Care (LINC) intervention utilized peer-led strengths-based case management to motivate HIV-infected patients in addiction treatment to obtain HIV care. This paper describes the protocol of a randomized controlled trial evaluating the effectiveness of the LINC intervention in St. Petersburg, Russia. Methods/design Participants (n = 349) were recruited from the inpatient wards at the City Addiction Hospital in St. Petersburg, Russia. After completing a baseline assessment, participants were randomly assigned to receive either the LINC intervention or standard of care. Participants returned for research assessments 6 and 12 months post-baseline. Primary outcomes were assessed via chart review at HIV treatment locations. Discussion LINC holds the potential to offer an effective approach to coordinating HIV care for people who inject drugs in Russia. The LINC intervention utilizes existing systems of care in Russia, minimizing adoption of substantial infrastructure for implementation. Trial Registration NCT01612455